金匱要略·婦人雜病脈證幷治第二十二에 對한 硏究 - 이태호(Tae Ho Lee); 임동국(Dong Kook Lim); 고승욱(Seung Wook Koh); 정헌영(Heon Young Jeong); 금경수(Kyoung Su Keum) (동의생리병리학회지, 2008)
This study is concerned with examining the causes and symptoms of Woman various diseases and clearing up the situations of pulses and their treatment. Woman various diseases are said to be various kinds of diseases including the disorder of menstruation and genitals except pregnancy and postpartum diseases. The main contents are the penetration of heat into worm, the discharge of much blood, stomachache, and the postpartum cyst diseases. Among them, the nature of the diseases which often occur in the gynecology, such as the menstrual diseases and stomachache, were described comparatively in detail. The reason why heat penetrates into the worm is that the external germs come into it under its weakness. To treat it, heat should be removed and lumping blood should be sent out of body. Especially only after whether the disease is serious or not is examined, and just after the process of the disease is examined, the lumping blood can be eliminated. The ways to cure it by sweating a patient too much, getting him or her to vomit, or forcing him or her to be urinated too much, should be avoided. The disorder of menstruation, as the disease which most often occur among the diseases of gynecology, includes menstrual irregularity and blood discharge, and non-menstruation. Among them, non-menstruation and blood discharge are comparatively often discussed. When they are treated, lumping blood and cold energy should be cured well through getting rid of the lumping blood and making the blood vessel flow well. The difficult urination after childbirth, which comes from the weak urinary cist, makes symptoms such as the stuffy chest, the difficulty of lying down, and breathing with his or her back something. To urinate better, the ability of the urinary cist should be supplemented and improved. The principle of the treatment for Woman various diseases is to examine the situation of the pulse closely, then set up the way to treat it, and prescribe a patient. In this study, besides the treatment of Chinese herb medicine, the medicine for washing genitals and the medicine placed in the worm were used to cure Woman various diseases. This treatment is the beginning of the surgical treatment in the gynecology. This study is concerned with examining the causes and symptoms of Woman various diseases and clearing up the situations of pulses and their treatment. Woman various diseases are said to be various kinds of diseases including the disorder of menstruation and genitals except pregnancy and postpartum diseases. The main contents are the penetration of heat into worm, the discharge of much blood, stomachache, and the postpartum cyst diseases. Among them, the nature of the diseases which often occur in the gynecology, such as the menstrual diseases and stomachache, were described comparatively in detail. The reason why heat penetrates into the worm is that the external germs come into it under its weakness. To treat it, heat should be removed and lumping blood should be sent out of body. Especially only after whether the disease is serious or not is examined, and just after the process of the disease is examined, the lumping blood can be eliminated. The ways to cure it by sweating a patient too much, getting him or her to vomit, or forcing him or her to be urinated too much, should be avoided. The disorder of menstruation, as the disease which most often occur among the diseases of gynecology, includes menstrual irregularity and blood discharge, and non-menstruation. Among them, non-menstruation and blood discharge are comparatively often discussed. When they are treated, lumping blood and cold energy should be cured well through getting rid of the lumping blood and making the blood vessel flow well. The difficult urination after childbirth, which comes from the weak urinary cist, makes symptoms such as the stuffy chest, the difficulty of lying down, and breathing with his or her back something. To urinate better, the ability of the urinary cist should be supplemented and improved. The principle of the treatment for Woman various diseases is to examine the situation of the pulse closely, then set up the way to treat it, and prescribe a patient. In this study, besides the treatment of Chinese herb medicine, the medicine for washing genitals and the medicine placed in the worm were used to cure Woman various diseases. This treatment is the beginning of the surgical treatment in the gynecology. KCI Citation Count: 0